ANALISIS FAKTOR PENENTU KINERJA PEMERINTAH KELURAHAN (Suatu Studi Di Kecamatan Mapanget Kota Manado) - Pesoth, Willy (Sam Ratulangi University, 2014)
ABSTRACT : The performance of the government apparatus is a crucial issue often faced by localgovernments, especially at village level. The low performance of the government apparatus at theVillage district of Manado Mapanget not be separated from some of the determining factors, such asthe factor of education / skills, compensation, coordination, mentality and work discipline in runningthe administrative tools duties of government. This study aimed to find out there are at leastinfluence the factors of education / skills, compensation, coordination, mental attitudes and workdiscipline on the performance of district governments in Sub Mapanget.Based on the results of data analysis found that the average determinants, such as formaleducation, skills or formal education, kompensai, coordination, mental attitude and disciplineadministrative tool, is also still low Uncategorized. Thus, all proved decisive factor affecting thedevice performance Mapanget village in the District is still in the low category. This situationclearly affects the performance of the device itself, which village was still significantly lowerUncategorized.The results concluded that the factors of skill, compensation, coordination, mental attitude anddiscipline administrative tool, although still low but associated Uncategorized contributive andsignificant or very significant to the performance of administrative devices, especially in SubMapanget. This gives the meaning that if all the determinants is sought to be improved, it willencourage the improvement of administrative performance of the device itself.Keywords: determinant factors, performance of administrative tools